An Epidemiologic Analysis of Co-Occurring Alcohol and Drug Use and Disorders: Findings From the National Epidemiologic Survey of Alcohol and Related Conditions (NESARC) - Falk, Daniel (National Institute on Alcohol Abuse and Alcoholism, 2008)
The 2001–2002 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) sought to determine the prevalence of alcohol use and alcohol use disorders (AUDs), other drug use and drug use disorders (DUDs), and co-use and co-morbidity in the general adult U.S. population. Findings indicate that 5.6 percent of U.S. adults used both alcohol and drugs in the past year and that 1.1 percent had a co-morbid AUD and DUD. Alcohol use prevalence peaked between the ages of 25 and 44 and declined thereafter. The prevalence of other drug use, co-use, AUDs, DUDs, and co-morbid disorders was highest between the ages of 18 and 24 and declined steadily thereafter. Women and men showed similar trends for alcohol use, drug use, and co-use. Among ethnic/racial groups evaluated, Whites displayed the highest rates of alcohol use and American Indians/Alaskan Natives the highest rates of drug use. For AUDs, DUDs, and co-morbid disorders, rates were highest among American Indians/Alaskan Natives. The prevalence of drug use, weekly drug use, and DUDs increased with increasing levels of alcohol consumption and the presence of AUDs. The proportion of people with AUDs who had a co-morbid DUD varied considerably by drug type. These findings have important implications for the development of prevention and intervention approaches.